2012
DOI: 10.1039/c1md00232e
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and properties of trimethylaminophenoxy-substituted Zn(ii)-phthalocyanines

Abstract: The syntheses, photophysical properties and in vitro biological behavior of a series of nine Zn(II)-phthalocyanines (ZnPcs) bearing one to eight positively-charged trimethylaminophenoxy groups are reported. All ZnPcs are highly soluble in polar organic solvents, and show fluorescence and singlet oxygen quantum yields in the ranges 0.11–0.21 and 0.16–0.47, respectively. The cytotoxicity of the ZnPcs depends on both the number of charges and their site of substitution (α vs. β) on the Pc isoindole units; the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…Thus, metallophthalocyanines are more convenient for their use in PDT than the free base analogues. Most of the phthalocyanine optical, spectroscopic and electrochemical properties result from their electronic structure and can be tailored and tuned through structural modifications of the macrocycle [104,105].…”
Section: Metallophthalocyaninesmentioning
confidence: 99%
“…Thus, metallophthalocyanines are more convenient for their use in PDT than the free base analogues. Most of the phthalocyanine optical, spectroscopic and electrochemical properties result from their electronic structure and can be tailored and tuned through structural modifications of the macrocycle [104,105].…”
Section: Metallophthalocyaninesmentioning
confidence: 99%
“…The starting ZnPc 1 was prepared as we have recently reported, from reaction of the corresponding aminophenoxy-substituted ZnPc [19] with diglycolic anhydride in DMF [12]. Activation of the carboxylic acid of ZnPc 1 using DIEA, HOBt and TBTU in DMSO, followed by addition of the commercially available anti-CEA MAb in NaHCO 3 solution gave bioconjugate 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The UV-vis absorption spectra were measured on an Ultrospec 400 UV-vis spectrophotometer from Pharmacia Biotech. ZnPc 1 was prepared as recently reported [19, 12]. …”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that such short PEG groups possess lower conformational flexibility compared with larger PEGs, and therefore tend to minimize Pc aggregation, enhance fluorescence quantum yields and increase cellular uptake [18, 19, 37, 38]. In addition, these ZnPcs contain one or two hydroxyl groups or a dimethylamino functionality on the α-position(s); we have previously observed that ZnPcs substituted on the α- (rather than on the β-) positions tend to show higher phototoxicity [18, 39]. On the other hand, the zinc(II) ion was chosen due to its diamagnetic properties and the demonstrated ability of ZnPcs to generate singlet oxygen [18, 26, 39].…”
Section: Introductionmentioning
confidence: 99%